Pengaruh Kepemimpinan Transformasional dan Work Life Balance terhadap Motivasi Kerja dengan Beban Kerja sebagai Variabel Mediasi: Studi pada Guru Perempuan di SMA/SMK Kecamatan Ciledug, Tangerang, Banten - Shania Fajriyah; Slamet Mudjijah (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the effect of transformational leadership and work-life balance on the work motivation of female teachers at senior high schools/vocational high schools in Ciledug District, Tangerang City, Banten, with workload as a mediating variable. The research used a survey method with saturated sampling technique on 139 female teachers. Data were collected through a questionnaire that had been tested for validity and reliability. Data analysis was performed using Partial Least Square (PLS) version 4.1.1.2 through outer model evaluation, inner model, and path analysis. The results showed that transformational leadership and work-life balance had a significant effect on work motivation. Transformational leadership and work-life balance were proven to have a significant negative effect on workload. Workload also affected work motivation and acted as a mediating variable in the relationship between transformational leadership and work motivation, as well as between work-life balance and work motivation. The coefficient of determination shows that transformational leadership and work-life balance can explain 42.1% of the variation in workload, while transformational leadership, work-life balance, and workload together explain 38.3% of the variation in work motivation.